Non-Penal Conflict Resolution and Islamic Legal Culture: Evidence from Sunni–Shia in Indonesia - Muwaffiq Jufri; Paul Atagamen Aidonojie; Ousu Mendy; Ebrima Sarr; Raphael Daoud Jackson-Ortiz (Unnes Law Journal, 2026)
This study aims to analyze the potential success of a religion-based conflict-resolution approach grounded in non-penal policies of Islamic legal culture. The use of this method is important for resolving the Sunni-Shia conflict in Sampang Regency. This study contributes to the development of guidelines for regional governments on the use of non-legal policies to resolve religious conflicts. This study uses empirical legal research methods with a socio-legal and anthropo-legal approach. The findings of this study reveal that penal policies for conflict resolution are ineffective in resolving conflicts quickly and only perpetuate stigma regarding which religious sects are right and which are heretical. This study also reveals that, when attempting to resolve and prevent disputes, non-penal methods grounded in Islamic legal culture are more effective in resolving religious conflicts more quickly and peacefully, with a familial approach, while avoiding violent means in resolving religious sectarian differences. This study concludes that the non-penal approach should be strengthened by assigning a role to local actors within the Madurese tradition to conduct the resolution process, so that former Shia followers, who are still being rejected, can be appropriately addressed. This study recommends that the government adopt a non-penal approach to facilitate the immediate completion of the post-conflict reconciliation and reconstruction process.